2020
DOI: 10.1002/lno.11453
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in δ13C of coral reef macroalgae

Abstract: Macroalgae are important components on coral reefs that underpin food webs but are also indicators of declines in coral reef condition. The sensitivity of macroalgal communities to environmental factors, including climate and pollutants from the land, is important for the future state of coral reefs. We assessed regional variation in the photosynthetic physiology of macroalgae on the Great Barrier Reef and Moreton Bay, Queensland, Australia, using δ 13 C, tissue chemistry, and metabolic indicators over broad e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
(129 reference statements)
1
4
0
Order By: Relevance
“…Our regression models showed that morphofunctional groups have a R 2 adjusted =0.34, and increase to genus (R 2 adjusted =0.41,) and to species (R 2 adjusted =0.46). This result is consistent with reported by Lovelock et al, (2020), which found that 66% of δ 13 C variability was explained by taxonomy. Although morphofunctional groups could explain less than genus or species, it is a great tool to increase the possibility of analyzes on a big spatial scale, especially when the species distribution could be limited.…”
Section: Morphofunctional Groups and δ 13 Csupporting
confidence: 93%
See 2 more Smart Citations
“…Our regression models showed that morphofunctional groups have a R 2 adjusted =0.34, and increase to genus (R 2 adjusted =0.41,) and to species (R 2 adjusted =0.46). This result is consistent with reported by Lovelock et al, (2020), which found that 66% of δ 13 C variability was explained by taxonomy. Although morphofunctional groups could explain less than genus or species, it is a great tool to increase the possibility of analyzes on a big spatial scale, especially when the species distribution could be limited.…”
Section: Morphofunctional Groups and δ 13 Csupporting
confidence: 93%
“…The Gulf of California is a subtropical, semi-enclosed sea of the Pacific coast of Mexico, with exceptionally high productivity being the most important fishing regions for Mexico and one of the most biologically diverse worldwide marine areas (Zeitzschel, 1969;Espinosa-Carreón and Valdez-Holguín 2007;Lluch-Cota et al, 2007;Páez-Osuna et al, 2017). GC represents only https://doi.org/10.5194/bg-2021-50 Preprint.…”
Section: Gulf Of California Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these factors may mean that large diatoms are better suited to lower irradiances. For example, a small number of non‐CCM macroalgal species exhibit exclusive CO 2 diffusive uptake (Raven et al., 1995) with a corresponding low light spatial distribution in deep habitats or beneath dense canopies where carbon demands of individuals are lower (Cornwall et al., 2015; Hepburn et al., 2011; Lovelock et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CCMs that allow marine macroalgae to utilize HCO 3 will likely still be favored under elevated atmospheric pCO 2 (~1,000 matm) predicted by 2100 due to HCO 3 remaining the dominant Ci species (>90%) of total DIC (~2,200 mmol kg -1 ) in seawater (Hartin et al, 2016), supported by the conservative CCM trait evolutionarily across marine macroalgae phyla (Stepien et al, 2016). Regardless of CCMs, higher seawater pCO 2 is likely to increase CO 2 as an Ci source for macroalgae as observed across latitudinal and coastal gradients of dissolved CO 2 (Lovelock et al, 2020, Stepien, 2015, Hofmann & Heesch, 2018.…”
Section: Introductionmentioning
confidence: 91%